2011
DOI: 10.4236/ait.2011.12005
|View full text |Cite
|
Sign up to set email alerts
|

WiFi/WiMAX Seamless Convergence with Adaptive Vertical Handover for Continuity of Internet Access

Abstract: The next generation of the wireless networks will consist of several overlapping tiers. Provision of undisrupted communication to mobile users is a challenging task. Handover delay is one of the problematic issues that users are faced in the heterogeneous networks. However, in the case of both the WiMAX and the WiFi technologies which are located at the same base station (BS), the vertical handover (VHO) delay will be less as compared with the two conventional WiMAX/WiFi heterogeneous networks with two differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…In [28], an access network selection algorithm that uses AHP and TOPSIS was proposed, but crucial QoS parameters such as RSS and available bandwidth resources were not considered in the selection process. However, it has been shown that the available bandwidth, received signal quality, battery life of the MT, security level, cost of service per byte, and distance between MT and BS are important parameters when considering vertical handoff decisions [29][30][31].…”
Section: Related Workmentioning
confidence: 99%
“…In [28], an access network selection algorithm that uses AHP and TOPSIS was proposed, but crucial QoS parameters such as RSS and available bandwidth resources were not considered in the selection process. However, it has been shown that the available bandwidth, received signal quality, battery life of the MT, security level, cost of service per byte, and distance between MT and BS are important parameters when considering vertical handoff decisions [29][30][31].…”
Section: Related Workmentioning
confidence: 99%
“…These include received signal strength which is closely related to service quality and can be measured (Chen et al 2009), network connection time which refers to the extent that a user remains connected to the current point of connection, available bandwidth which is a calculation of existing data communication resources, expressed in bit per second (Inayat et al, 2005;Alkhayat et al, 2009), power consumption which becomes a critical issue when the battery of MT is low (Syuhada & Mahamod, 2008;Chandralekha & Behera, 2011), monetary cost which must be considered in making handover decisions as every network has its own pricing policies (Chen & Hsut, 2006;Saeed, 2011), security which is considered before selecting one network over another when the integrity of the transmitted data is vital, user preferences since a user's individual liking could lead to the selection of one type of network over the other networks (Lee et al, 2007;Tomar, 2009). …”
Section: Introductionmentioning
confidence: 99%